Displacement: Critical insights from flood-affected children. (July 2018) - Mort, Maggie; Walker, Marion; Williams, Alison Lloyd; Bingley, Amanda
Abstract: Little is known about how children and young people are affected by evacuation following flooding. Participatory research using creative methods allowed us to elicit flood stories and recovery pathways over time. We found that children's relationships with space and place were severely challenged following evacuation from home. They suffered losses, including loss of agency, friendship networks and familiar space. They experienced distress, anxiety and disillusionment with societal responses. Sustained attention by flood risk and recovery agencies is required to address children's ongoing needs following evacuation. From policymakers recognition is overdue that young people are citizens who already contribute to community flood response and so need to be more explicitly consulted and included in the development of flood risk management. Highlights: Creative methods assist in eliciting children's flood stories. Children's relationships with space and place are severely challenged, particularly where they are evacuated from home. They experienced distress, anxiety and disillusionment with societal responses. Sustained attention by flood management, insurance and recovery agencies is required to address children's ongoing needs following evacuation. Young people already contribute to community flood response; so should be consulted and included in policy development.